1992
DOI: 10.1037/0021-843x.101.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the frequent nightmare sufferer.

Abstract: Previous research has found that persons who experience frequent nightmares score highly on scales that measure psychotic symptomatology. Neurotic symptoms have also been implicated as correlates of nightmare frequency. In this study, 30 adult lifelong nightmare sufferers were compared with 30 control subjects, matched for age, sex, and socioeconomic status. Subjects were asked to record all dreams for 1 month and to complete the Minnesota Multiphasic Personality Inventory (MMPI) and the Eysenck Personality Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 17 publications
10
70
0
1
Order By: Relevance
“…Three independent investigations (Berquier & Ashton, 1992;Blagrove et al, 2004;Zadra & Donderi, 2000) demonstrated significantly higher levels of neuroticism as measured by the Eysenck Personality Questionnaire (EPQ; Eysenck & Eysenck, 1975) for individuals with frequent nightmares compared with controls. Similarly, Claridge, Davis, Bellhouse, and Kaptein (1998) reported a relationship between EPQ neuroticism and nightmare distress, although they did not assess nightmare frequency.…”
Section: Nightmares Are Associated With Neuroticism and Global Symptomentioning
confidence: 99%
“…Three independent investigations (Berquier & Ashton, 1992;Blagrove et al, 2004;Zadra & Donderi, 2000) demonstrated significantly higher levels of neuroticism as measured by the Eysenck Personality Questionnaire (EPQ; Eysenck & Eysenck, 1975) for individuals with frequent nightmares compared with controls. Similarly, Claridge, Davis, Bellhouse, and Kaptein (1998) reported a relationship between EPQ neuroticism and nightmare distress, although they did not assess nightmare frequency.…”
Section: Nightmares Are Associated With Neuroticism and Global Symptomentioning
confidence: 99%
“…Both Berquier and Ashton (1992) and Kelly (2016) found that nightmares were associated with scores on broad-spectrum personality instruments which might reflect personality maladjustment and related psychological symptomology. Recently, Sheaves et al (2016) produced similar findings and observed that nightmares were related to several markers of mental illness in a college student sample.…”
Section: Original Articlementioning
confidence: 99%
“…2,9,[11][12][13][14][15] Additionally, nightmares are associated with a heightened risk of suicidal ideation in both military and civilian populations. 16,17 As sleep and psychiatric disorders are frequently reported in United States military personnel, this population may have a high prevalence of nightmare disorder (NDO).…”
mentioning
confidence: 99%